مدخل مقاصدي للاجتهاد: حل التعارض ودلالة المقصد أنموذجين - جاسر عودة (International Institute of Islamic Thought, 2013)
يقترح هذا البحث توظيف منهجية مقاصدية للاجتهاد، ويضرب أمثلة على إعمال المقاصد في الاجتهاد في مسألتين أصوليتين مهمتين، هما: حل التعارض الظاهري بين روايات الحديث النبوي، وفهم دلالة الأحاديث عن طريق النظر إلى المعاني والغايات المقصودة من ورائها. وينتقد البحث في ثناياه المنهجية التي تقتصر على الدلالات الظاهرة للألفاظ، دون معانيها المقصودة التي يستدل عليها بالسياق، كما يبطل المنهجية التي تدّعي "تأرُّخ" (أو تاريخانية) النص الشرعي من كتاب وسنة، بحجة فصل الدال عن المدلول، أو ما سمي بعملية التفكيك. The paper proposes using a methodology of maqasid (intent) in making ijtihad, and introduces examples for the realization of maqasid of the Islamic law. The applications at hand are two prime juridical issues namely, the resolution of conflicting narrations of Hadith, and the understanding of the intent of the text. The paper criticizes the reasoning methodology that restricts itself to the literal implications of the text and not their intended meanings, as well as the methodology that "historicizes" the revealed text based on separating the signified from the signifier or the so-called "deconstruction" process.